The last million : Europe's displaced persons from World War to Cold War - Nasaw, David (Penguin Press, 2020)
In May of 1945, German forces surrendered to the Allied powers, effectively putting an end to World War II in Europe. But the aftershocks of this global military conflict did not cease with the signing of truces and peace treaties. Millions of lost and homeless POWs, slave laborers, political prisoners and concentration camp survivors overwhelmed Germany, a country in complete disarray. British and American soldiers gathered the malnourished and desperate foreigners, and attempted to repatriate them to Poland, Estonia, Latvia, Lithuania, Ukraine and the USSR. But after exhaustive efforts, there remained over a million displaced persons who either refused to go home or, in the case of many, had no home to which to return. They would spend the next three to five years in displaced persons camps, divided by nationalities, temporary homelands in exile, with their own police forces, churches, schools, newspapers and medical facilities. The international community couldn't agree on the fate of the Last Million, and after a year of fruitless debate and inaction, an International Refugee Organization was created to resettle them in lands suffering from labor shortages. But no nations were willing to accept the 200,000 to 250,000 Jewish men, women and children who remained trapped in Germany. In 1948, the United States, among the last countries to accept anyone for resettlement, finally passed a Displaced Persons Bill, but as Cold War fears supplanted memories of World War II atrocities, the bill only granted visas to those who were reliably anti-communist, including thousands of former Nazi collaborators, Waffen-SS members and war criminals, while barring the Jews who were suspected of being Communist sympathizers or agents because they had been recent residents of Soviet-dominated Poland. Only after the passage of the controversial United Nations resolution for the partition of Palestine and Israel's declaration of independence were the remaining Jewish survivors finally able to leave their displaced persons camps in Germany.